EXPLORING THE EXPERIENCES OF NURSES WHO PROVIDE CARE TO SURVIVORS OF STROKE WITHIN A SPECIALIZED STROKE REHABILITATION UNIT - Barreca, Susan (My University, 2005)
The purpose of this hermeneutic phenomenological study was to systematically explore and gain understanding into the perceptions, beliefs, and feelings of nurses who provide care to survivors of stroke within a specialized stroke rehabilitation unit of a tertiary care hospital. From the literature and my experience on the stroke team, there seemed to be poor relationships among the nurses and survivors of stroke, their families, and other stroke team members. A first step in improving team effectiveness and quality of care to survivors of stroke is to improve interpersonal and interdisciplinary communication. As I began to interact more with the nurses and think about their concerns, I realized that I knew very little about their experiences in providing care to individuals following a stroke. Six themes revealed that these nurses: (1) enjoyed their work; (2) considered their role pivotal to the rehabilitation process; (3) found it difficult to let patients struggle to complete their every day tasks; (4) believed these patients get short-changed in their rehabilitation nursing care; (5) felt others did not appreciate their role in stroke rehabilitation; and yet (6) maintained a positive outlook. A new literature search produced four sensitizing concepts that reflected (i) the historical roots of nursing within a institutional patriarchal setting; (ii) the stereotyping of nursing as a female-orientated job akin to the role of wife and mother, thus leading to its invisibility; (iii) societal devaluation of those nursing tasks dealing with bodily waste by products; and (iv) lastly, the combination of all the above factors that stifle the nurses’ attempts to gain empowerment and to have more control over their work life. By exploring the nurses’ concerns, I hope to create an atmosphere of thoughtfulness that will improve clinical practice within the stroke rehabilitation unit and facilitate the empowerment of the nurses to become equal partners in providing care to individuals following a stroke.
EXPERIENCES OF NURSES PROVIDING CARE TO SURVIVORS OF STROKE
Keywords: Healthcare; Stoke Rehabilitation; Gender; Typology